(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Type 2 diabetes mellitus (T2DM) is among the few disorders that have been linked with an increased risk of cognitive decline and dementia in the elderly. While the damaging effects of sustained high blood sugar levels have been known for quite some time, recent studies point to glycemic variability changes in blood sugar levels over a period as possibly having a more negative impact on the brain. Nevertheless, there is always a lack of data from South Asian groups. Objective: Evaluate the link between glycemic variability and dementia in elderly patients with type 2 diabetes mellitus. Methods: A cross-sectional observational study was carried out at the Department of Diabetes and Endocrinology, Lady Reading Hospital, Peshawar, from 1st January, 2025 to 30th June, 2025. A total of 288 type 2 diabetic elderly patients (≥60 years) were included. Glycemic variability was determined by fasting plasma glucose and HbA1c serial measurements from the last year. Cognitive function was assessed by standardized cognitive assessment tools, while dementia was diagnosed based on clinical criteria. To determine the correlation between glycemic variability and dementia, a multivariable logistic regression analysis was done while adjusting for the confounders. Results: Dementia was diagnosed in 25.9% of the total study population. It was found that people with dementia had significantly more blood sugar fluctuations compared to people without dementia. After adjustment, the extent of variation in HbA1c and fasting glucose was independently linked to the risk of dementia. It was noted that dementia rates kept increasing in a dose-response manner across the quartiles of glycemic variability. Conclusion: Glycemic variability is one of the most important independent factors associated with dementia in elderly patients with type 2 diabetes. The present findings indicate that, just reaching the glycemic targets, it is essential to keep blood glucose fluctuations under control for maintaining cognitive function in elderly diabetic individuals